Team Psychological Needs and Radical versus Incremental Creativity of Work Teams. Issue 3 (27th May 2021) - Sung, Sun Young; Choi, Jin Nam
ABSTRACT: This study distinguishes between radical and incremental creativity at the team level. In addition, group composition in terms of members' psychological needs is identified as a distinct driver of radical and incremental team creativity. Statistical analysis based on multisource data of 65 work teams shows that (a) team-level need for achievement has a negative main effect on radical team creativity, which disappears in teams with optimistic leaders; (b) team-level need for affiliation has a negative main effect on incremental team creativity, which becomes positive when teams possess high social competence; and (c) team-level need for power is positively related to radical and incremental team creativity. Our analysis demonstrates the multifaceted nature of team creativity and the distinct implications of team-level psychological needs for team creativity.